The local cellular response to Human Papillomavirus focuses on basal layer restoration as visualized in situ by specific cellular neighborhoods near infected cells - Slieker, Roderick C.; Abdulrahman, Ziena; Santegoets, Saskia; van Poelgeest, Mariette I. E.; Welters, Marij J. P.; van der Burg, Sjoerd H. (Frontiers in Immunology, 2025)
BackgroundHuman papillomavirus type 16 (HPV16) is known to deregulate and cause hyperproliferation of the infected epithelium, but its full effect on the host’s tissue has remained elusive as earlier comprehensive studies were restricted to in vitro models.AimThe aim of the current study was to study HPV16-induced tissue changes in vulvar tissue in its full natural context by using single-cell spatial transcriptomics.MethodsWe applied spatial single-cell spatial transcriptomics to formalin-fixed paraffin-embedded healthy vulvar tissue (n=5) and HPV16+ high grade vulvar lesions (vHSIL, n=31).ResultsMore than 415,000 individual cells were identified and annotated in situ, to create complete digital atlases of the healthy vulvar and HPV16+ vHSIL tissues for comparison. Two subpopulations of basal cells were identified, one of which lined the basal membrane of healthy tissue, the other is characterized by a transcriptomic signature like HPV16-infected keratinocytes and upregulated inflammatory genes and observed predominantly in vHSIL. Epithelial cells in the parabasal layers of vHSIL upregulated the expression of genes associated with inflammation and proliferation. Importantly, HPV16 profoundly remodeled stromal fibroblasts, endothelial, and immune cells, reorganizing them into distinct cellular neighborhoods of which three dominated vHSIL. A regenerative niche adjacent to the basal layer, a perilesional niche characterized by immune suppression, and a more distal niche enriched for adaptive immune activity.ConclusionIn conclusion, spatial analysis reveals that HPV16 infection orchestrates a coordinated tissue response, driving basal layer restoration while locally suppressing immune activation to prevent pathological damage.